Epidemiology of Barrett’s oesophagus and oesophageal adenocarcinoma - Perez, Nancy; Taylor, William (Medical Studies/Studia Medyczne, 2019)
Barrett’s oesophagus is a condition characterised by metaplastic changes in the oesophagus and is a precursor to oesophageal adenocarcinoma. Oesophageal adenocarcinoma is recognised as being responsible for an increasing number of cancer-related deaths, especially in the western world. A deluge of risk factors have been described in the literature. Some of the important ones include gastroesophageal reflux disease, Helicobacter pylori infection, lifestyle factors like alcohol consumption, smoking, and dietary factors, and metabolic diseases like obesity. It also poses challenges in diagnosis and treatment despite recent advances in diagnostics, surgery, and other therapies. This is a narrative review of the findings of multiple studies that were retrieved from electronic databases like PubMed, Google Scholar, Scopus, Medline, Embase, and Cochrane. We summarise the current knowledge regarding the epidemiology and various risk factors for the development of Barrett’s oesophagus and oesophageal adenocarcinoma.1